Study on the Removal Technology of Trichloramine from Drinking Water Using Ultraviolet Light - Takanami, Ryohei; Yoshida, Shiho; Nagare, Hideaki; Echigo, Shinya; Hashiguchi, Ayumi (Journal of Water and Environment Technology, 2025)
Trichloramine (NCl3) is an inorganic chloramine that causes a pungent chlorine-like odor, and it is difficult to remove its precursors (nitrogen organic compounds and/or ammonia) completely from water. Powdered activated carbon, ozonation, and UV treatment have been applied for decomposing NCl3, but free chlorine was also decomposed. So, it is necessary to develop a technique that can selectively control NCl3 without losing free chlorine. UV light-emitting diodes (265, 280, and 300 nm) and plasma emission UV sheet (347 ± 52 nm, hereafter 350 nm) were compared to find the optimal wavelengths that decompose NCl3 but not free chlorine. As a result, 90.6, 96.7, 92.5, and 77.8% of NCl3 were removed at 265, 280, 300 (3,600 mJ/cm2), and 350 nm (14,400 mJ/cm2), respectively. On the other hand, free chlorine at neutral pH (hypochlorous acid is dominant) and slightly alkaline pH (hypochlorite ion is dominant) was not decomposed at 350 nm, but at other wavelengths (i.e., 265, 280, and 300 nm) the removals were more than 64%. Therefore, UV radiation at 350 nm can be candidates to remove NCl3 while maintaining free chlorine. However, this method requires high input energy, and further study is needed for evaluating the practical applicability of this method by considering optimal reactor design.